Ergonomics intervention in manual milling operation workstation - Chow, Che Hoe (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Manufacturing sector is vital in driving malaysia's economy and this project's focus is to induce the ergonomics and safety concerns in the sub-element of this sector. Manual milling operation is a precise and accurate job that requires the operators stay alert even in the prolonged working hours. The milled product is vital since manual milling operation is a pre-machining process where follow by other machining processes.